A functional natural dentition for all – and for life? The oral healthcare system needs revision. (16th July 2013) - Fejerskov, O.; Escobar, G.; Jøssing, M.; Baelum, V.
Summary The cost of dental care adds to the costs of the already overburdened health sector. Do we – as patients and as society –receive oral health care that is both aligned with the actual disease experience and also, critically based on up‐to‐date scientific knowledge about the major oral diseases? In many places, the practice of dentistry reflects a response to disease patterns that once existed and is based on diagnostic and therapeutic approaches that are no longer valid. Instead, a new cadre of dental professionals is needed, one that is capable of meeting the actual health needs of our populations. This cadre should ensure that patients maintain a functioning dentition from cradle to grave based on cost‐effective disease control principles. There is an urgent need to: (i) reconsider the roles of the different oral health cadres involved in the provision of oral health care; (ii) integrate oral health into general healthcare services; and (iii) restructure the training of oral health personnel. We advocate a radical reform of the oral healthcare system involving the training of two new types of professionals integrated with the general healthcare system: The oral healthcare provider – a highly skilled professional specialised in the diagnosis and control of oral diseases and with a profound understanding of oral health as part of general health – and the oral clinical specialist – whose role is the provision of advanced oral rehabilitation, able also to treat people with complex chronic diseases and multiple medications.